Women's intergenerational intimate partner violence and household child abuse in Burma (Myanmar) - Stephanie Spaid Miedema; Aye Thiri Kyaw (Elsevier, 2022)
Intimate partner violence (IPV) and child abuse are prevalent in Burma (Myanmar). However, gaps exist in our understanding of intergenerational cycles and co-occurrence of violence, and whether patterns of violence vary by women and children's life course transitions and developmental stages. Using data from the 2015-2016 Demographic and Health Survey, we estimated structural equation models to evaluate the pathways between women's exposure to IPV perpetrated by her father against her mother (maternal abuse), her own past-year experiences of IPV, attitudes toward IPV, and household child discipline practices. We ran stratified analyses by women's age at first birth and child's age to assess whether intergenerational cycles and co-occurrence of violence in the household vary by pivotal life events and development stages. Maternal abuse was directly and indirectly associated with women's past-year exposure to physical and/or sexual IPV and children's exposure to physical or emotional child abuse by a caregiver in the household. Stratified models indicated significant intergenerational cycles of IPV and co-occurrence of IPV and child abuse among women who experienced first childbirth before age 23, and among women living with older children. We conclude that synchronized efforts to prevent violence against women and violence against children are integral to addressing cyclical and co-occurring patterns of violence in Burma (Myanmar). Violence prevention efforts might consider developmental stage and life course factors that may intensify risk of intergenerational violence.